Integrated Vocational Training Centres - Carmen López-Fuensalida Moya (ADIDE Federación, 2007)
Integrated Vocational Training Centres are the last link upon which all the actions and instruments laid out by the Organic Act on Qualifications and Vocational Training must be materialized. These centres are regarded in the Organic Act as those which implement their vocational training offer with some training activities aiming at the acquisition of Diplomas and Certificates of occupational standards referring to the National Catalogue of Occupational Qualifications. The Act also lays upon the hands of the Educational Administrations of Spanish autonomous regions the responsibility for the creation and official permission of these centres, under the legal requirements they settle. Nevertheless, the flexible and open approach of this article to the creation of this type of centres is quite suitable, though the vital importance of these centres to develop all the formative actions scheduled in the Act is not clearly enough pointed out. The main objectives of the integrated Vocational Training Centres are two: first, the qualification and even re-qualification of people as part of the drawing-up of their personal lifelong learning process, and second, the creation of a space for cooperation, dialogue and interaction between the Vocational Training System and the production system.